The Sinking of German Submarines in the Black Sea During World War II and the Mandatory Accommodation of Military Personnel in Turkey - Umut Cafer Karadoğan (Yakın Dönem Türkiye Araştırmaları)
During the Second World War, as a result of the events that took place around the strategic geography of Turkey, the United Kingdom; the United States of America, and, from time to time, Germany tried to implement harsh policies against Turkey. This study focuses on the following themes: Germany’s efforts to transport its submarines to the Black Sea by land and river within the framework of Operation Barbarossa, which was designed as a part of its plan to destroy the Soviet Union; Germany’s sinking of its submarines in order not to surrender to the Russians as a result of the failures it experienced there; the capture of the aforementioned submarines’ military personnel when they landed, wereinterned, and then subjected to compulsory stay in different camps in Turkey; the legal process followed by the Turkish government of the period; the attitude of the Turkish government toward German soldiers; the exchange method of these soldiers; and Turkey’s viewpoint regarding the war and parties of the war.